ANALISIS PERTIMBANGAN HUKUM PENETAPAN PERKARA NO. 155/PDT.P/2023/ PN.JKT.PST TENTANG PERKAWINAN BEDA AGAMA - NIM. A1011181163, IHZA RIANSA (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThe judge's legal consideration regarding the registration of interfaith marriages according to Indonesian positive law is Article 35 letter (a) of Law Number 23 of 2006 concerning Population Administration which reads: